Integrated Thematic Learning Based On Discovery Learning in Excellent Islamic School Bukittinggi - Sasriyanti, Rika; F, Farida; Efendi, Jon (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to describe the increase in activity and comprehensive thematic learning outcomes based on discovery learning at Excellent Islamic School at grade IV, Bukittinggi. Due to a number of factors that cause low activity and learning outcomes, encouraging research motivation, among others, students are not accustomed to learning to find information on their own, are not accustomed to collecting and processing facts or information by themselves, and proving that the knowledge received is correct or incorrect. This type of research is a classroom action research using qualitative and quantitative approaches. The research procedure was preceded by planning, implementing, observing, and reflecting. The research data is in the form of observations of the learning process and the results of the action. This research was conducted in the second semester of the 2019/2020 academic year. The research subjects were 26 grade IV students consisting of 12 boys and 14 girls. The results of the research on the visual activity of students in cycle I got good category (78%) and cycle II got very good category (achievement 89%) with an increase of 11%. The oral activity increase 16% from 62% at cycle 1 to 78% at cycle II. The learning outcomes of students in cycle 1 were categorized as poor and in cycle II the average of the three subjects was categorized as good. From the research results it can be concluded that learning using the Discovery Learning model can increase the activity and learning outcomes of students in grade IV of Excellent Islamic School Bukittinggi.